Integrating sustainability into art and design education: curriculum development - Mapar, Mahsa (2023)
Sustainability is an important factor in art educa>on. Several ar>sts, in line with the UN Agenda 2030, have embraced the idea of art for sustainability in different ways to reflect the protec>on of natural landscapes, the consequences of industrializa>on and the growth of ci>es, and the use of resources. However, these topics are rarely taught to art students in higher educa>on, considering belonging to science subjects. On the other hand, to change art students' aLtudes toward sustainability, it is essen>al that social conscience and responsibility emerge from both knowledge and values. In this context, the ERASMUS+ ARDES project - Short Learning Programme (SLP) for ARt and DEsign and Sustainability with special focus on environment and climate change (CC) (2022-2024)- has been set up through a strategic partnership among 5 European partners: MyDocumenta (Spain), European University Cyprus (Cyprus), Universidade Aberta (Portugal), EINA (Spain) and the associated partner LABA Valencia (Spain). The project intends to provide open educa>onal resources for art students by integra>ng knowledge and values associated with sustainability and CC through art ac>vi>es, design techniques, and digital solu>ons. This paper aims to present the ini>al results of the curriculum development of this SLP through formal learning modules and extracurricular community work concerning sustainability and CC. The SLP, made of 156 academic hours plus an extracurricular community ac>vity, consists of 3 main modules: i) Module 1- Art, Design, Sustainability, and CC within historical and contemporary contexts; aiming to introduce the concepts of sustainability, the link with art and design, and sustainability assessment methods in art and design context; ii) Module 2- Art and Design for Communica>ng Sustainability and CC; aiming to use art and design as strategic tools for u>liza>on of visual communica>on, thus helping students to compile design projects concerning sustainability and CC; and iii) Module 3- Digital tools for the interac>ve engagement of audiences with Art and Design; aiming to introduce the concepts and applica>on of big data and the principles of audience engagement. Two learning plans were developed: 1) a "Module Plan" containing the modules objec>ves, competencies, essen>al ques>ons, resources, and assessment methods, and 2) a “Lesson Plan” covering the details of the educa>onal materials and ac>vi>es in each lesson. Various learning materials were developed, including text, slides, videos, and engaging tools. Also, diverse individual/collabora>ve ac>vi>es were designed, classified from project-based ac>vi>es, reflec>on on exis>ng art produc>ons, designing artwork, working with European and local databases, and live performance, all in the concept of sustainability and CC. In the next step (Oct 2023), the SLP will be piloted in partner Universi>es, targe>ng postgraduate students in art studies. The effec>veness of the training will be later assessed through a ques>onnaire. It is expected that by the end of the training, the students will be able to recognize how sustainability and CC integrate into the concepts of art and design, to later enhance their mo>va>on, opportunity, and ability for sustainable ac>ons in society, thus contribute to SDG 13, target 13.3 and SDG4, target 4.7.